1998
DOI: 10.1180/000985598545499
|View full text |Cite
|
Sign up to set email alerts
|

Kaolinite-to-dickite reaction in sandstone reservoirs

Abstract: A B S TRACT: The SEM, XRD, FFIR and DTA analyses of different size-fractions of clay material from sandstone reservoirs which have experienced a large range of burial conditions have been used to examine the different steps of the depth-related kaolinite-dickite reaction. Dickite progressively replaced kaolinite within a range of burial depths estimated between about 2500 m and 5000 m. The kaolinite-to-dickite reaction proceeds by gradual structural changes concomitant to crystal coarsening and change from boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(64 citation statements)
references
References 29 publications
6
53
0
Order By: Relevance
“…The kaolinite-dickite transition is observed in uncemented sandstone at 3240 m and is characterized by the progressive replacement of vermiform kaolinite by blocky dickite crystals (Figure 14). The depth of the transition is similar to the depth interval (2.8-3.6 km) proposed by Ehrenberg et al (1993) andBeaufort et al (1998) in the sandstone reservoirs from the continental platform of Norway and from the Rotliegend Formation, respectively. Ehrenberg et al (1993) suggested that the kaolinite-dickite transition is temperature dependant and that it occurs at -120~…”
Section: Kaolinite-dickite Transformationsupporting
confidence: 82%
“…The kaolinite-dickite transition is observed in uncemented sandstone at 3240 m and is characterized by the progressive replacement of vermiform kaolinite by blocky dickite crystals (Figure 14). The depth of the transition is similar to the depth interval (2.8-3.6 km) proposed by Ehrenberg et al (1993) andBeaufort et al (1998) in the sandstone reservoirs from the continental platform of Norway and from the Rotliegend Formation, respectively. Ehrenberg et al (1993) suggested that the kaolinite-dickite transition is temperature dependant and that it occurs at -120~…”
Section: Kaolinite-dickite Transformationsupporting
confidence: 82%
“…Our observation is, when kaolinite was harshly treated with salts particularly, NaCl a change in the order of arrangement of kaolinite occurred such that the surface area for intercalation is increased due to well arrangements of functional layers. Similarly, it was observed that particles with pseudohexagonal morphology in NaKP predominates over those with vermiform morphology; a similar observation was found by [31]. Moreover, the DMSO intercalated kaolinite exhibited a decreased compactness between layers where the distance was widened (Figure 4(c), red arrow).…”
Section: Sem Analysissupporting
confidence: 63%
“…For the most part, vermicular booklet morphology characterized the DMSO intercalated kaolinite with a very small appearance of the dispersed euhedral pseudohexagonal platelets. A similar observation though in a different setting made Baeufort to conclude that "aggregates of kaolin with blocky habits coexist with vermicular booklets, " an observation which we have considered to be valid in this work [31]. Such observation made us to sense that under certain conditions the appearance of vermiforms mixed with either stacked or dispersed euhedral pseudohexagonal platelets should be expected.…”
Section: Sem Analysismentioning
confidence: 64%
“…McAuley et al 1994;Osborne et al 1994). Kaolin polytypes (which for these purposes can be subdivided into kaolinite, intergrowths of kaolinite and dickite and pure dickite) become progressively more 'blocky' in appearance with increasing temperature (McAuley et al 1994;Beaufort et al 1998). In the WOS samples studied, the majority of kaolin had one of two morphologies:…”
Section: Sem and Xrd Studies Of Kaolin Polytypesmentioning
confidence: 99%
“…As feldspar dissolves during progressive burial, kaolin morphologies coarsen and become more euhedral due to recrystallization. Kaolinite coarsened by recrystallization (and intergrowths of kaolinite with dickite pseudomorphing kaolinite) are commonly referred to in the literature as 'blocky' or 'intermediate' kaolinite (Osborne et al 1994;Beaufort et al 1998). Intermediate kaolinite may, however, form by hydrothermal processes involving the illitization of early kaolinite by hot fluids (Lanson et al 1996), as well as by burial-related recrystallization.…”
Section: Sem and Xrd Studies Of Kaolin Polytypesmentioning
confidence: 99%